Gelatin microgels as a potential corrosion inhibitor carriers for self‐healing coatings: Preparation and codeposition. Issue 12 (12th August 2015) - Stankiewicz, A.; Jagoda, Z.; Zielińska, K.; Szczygieł, I.
Abstract : Co‐deposition of a coating with capsules containing a corrosion inhibitor is one of the methods to protect the material surface against corrosion. This generation of coatings can be regenerated in response to mechanical or chemical damage. The paper presents a method for preparing gelatin microgels that can be eco‐friendly corrosion inhibitor reservoir. The influence of temperature, stirring rate, an addition of surfactants (ionic and non‐ionic) on microgel quality has been studied. It has been found that the microgels obtained at 80 °C from the solution containing non‐ionic surfactant at concentration below its critical micelle concentration are the most stable and less polydisperse one. As a proof of concept, a Ni‐P\gelatin microgels hybrid coating has been obtained by electroless method.